Acceptability of HIV Screening in a Sample of International Students in the United States - Oluwasola Stephen Ayosanmi; Lorette Oden; Titilope Ayosanmi; Babatunde Y. Alli; Mei Wen; Jamie Johnson (International Journal of Maternal and Child Health and AIDS, 2020)
Background and Objectives: HIV transmission from persons unaware of their HIV status occurs more commonly than those who are aware of their status. Knowledge of one’s HIV status may encourage preventive behaviors. Anecdotal evidence suggests that many international students may be willing to accept HIV screening, but empirical evidence to support this claim is lacking. We sought to determine the willingness of international students in the United States (US) to accept HIV screening, if offered.